Relationship between endurance training and activity of the rectus femoris muscle in women with low bone mass - Ossowski, Z. (2016)
Changes in muscle strength and electromyographic activity of the lower limbs are pronounced with the aging process. Such changes are especially dangerous for women with low bone mass. So far there has been no conclusive evidence that Nordic walking (NW) offers biomechanical benefit for the lower extremities. Therefore, the purpose of the study was to evaluate the impact of NW training on the activity of the rectus femoris (RF) muscle in women with low bone mass. Conclusions – Nordic walking training may in part contribute to clinical improvement in muscle activities of the rectus femoris in women with osteopenia and osteoporosis. The study was conducted within the framework of the EU project entitled “Active lifestyles and predictors of risk for incapacity on senior population: RISINC2013-FRAILTY and RISINC2013-FALLS”.